An analog method of cross-talk compensation for a RGB wavelength division multiplexed optical link. (June 2018) - Chisholm, George; Leveneur, Jérôme; Futter, John; Kennedy, John
Graphical abstract: Highlights: An RGB WDM optical link is implemented using imperfect components. Cross-wavelength sensitivity of an RGB light-to-voltage sensor is compensated using an analog circuit. An iterative Monte-Carlo simulation approach is used to solve and optimize the op-amp compensation circuit. Cross-talk between channels is reduced to a point at which WDM PWM outperforms other encoding methods. Abstract: Pulse-width modulation (PWM) over optical fiber can be a very advantageous data transmission approach when an electrically isolated data link is required. The use of wavelength division multiplexing allows multiple data streams to be sent through a single fiber independently. The present investigation aims to demonstrate a novel approach to reduce cross-talk in a three-channel RGB optical link without the need for complex optical componentry. An op-amp circuit is developed to reduce the cross-talk so that the resolution of the PWM data is preserved. An iterative Monte-Carlo simulation approach is used to optimize the op-amp circuit. The approach is developed for a set of three PWM Hall effect magnetometers with 12-bit resolution and 128 Hz sampling rate. We show that, in these conditions, the loss of resolution due to cross-talk is prevented. We also show that the cross-talk compensation allows the RGB PWM link to outperform other transmission schemes.